Sensory quality of cascara brewing with ginger extract addition - Zalniati Fonna Rozali; Murna Muzaifa; Muliana Muliana; Faida Rahmi (AGROINTEK, 2024)
Coffee processing by-products can be used as a healthy beverage product called cascara. However, in Indonesia, consumers' preference for the taste of cascara is still unsatisfactory. This study aims to increase cascara's sensory quality with adding ginger extract. This study used a non-factorial Completely Randomized Design consisting of 4 ginger extract concentration treatments: J0 = 0%, J1 = 3%, J2 = 6% and J3 = 9%. Each treatment was repeated 3 times. The panelist acceptance was carried out for color, aroma, and taste to determine the sensory quality. Besides that, the pH value is also analyzed to determine the acidity level of the cascara brewing. The data were statistically analyzed using analysis of variance and DMRT further test at the 5% level. The results showed that adding ginger extract at various concentrations affected all panelists' acceptance of the cascara brewing drink and pH. Increasing the concentration of ginger added to increased acceptance of the color and taste of cascara brewing and the drink's pH. The highest aroma, taste, and pH values were obtained in the treatment with the highest concentration of 9% ginger. In comparison, the most favorable color was obtained in the treatment without adding ginger and adding ginger with a concentration of 9%. The results showed that adding ginger extract had a positive effect on improving the sensory quality of cascara brewing, and the addition of 9% ginger extract had the potential to develop as a functional drink.